2021
DOI: 10.1108/ijchm-05-2020-0372
|View full text |Cite
|
Sign up to set email alerts
|

Operation policy of multi-capacity logistic robots in hotel industry

Abstract: Purpose This paper aims to propose an operation policy of multi-capacity room service robots traveling within a hotel. As multi-capacity robots can serve many requests in a single trip, improved operation policy can reduce the investment cost of robots. Design/methodology/approach Using a mathematical model-based optimization technique, an optimal set of robots with minimum installation cost is derived while serving the entire room service demands. Through testing a variety of scenarios by changing the price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Customers need an easy and agile process for the booking and refunding process ( Tsang, Lai & Law, 2010 ). Promptness is important during the COVID-19 pandemic because travelers can become dissatisfied if the requests are not served within the allowed time ( Lee & Ko, 2021 ). Easy process is required by travelers when they requested services, especially during the COVID-19 pandemic ( Foroudi, Tabaghdehi & Marvi, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Customers need an easy and agile process for the booking and refunding process ( Tsang, Lai & Law, 2010 ). Promptness is important during the COVID-19 pandemic because travelers can become dissatisfied if the requests are not served within the allowed time ( Lee & Ko, 2021 ). Easy process is required by travelers when they requested services, especially during the COVID-19 pandemic ( Foroudi, Tabaghdehi & Marvi, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exact methods: Mix integer linear programming (MILP) was predominately implemented using optimization tools such as CPLEX [78,81,82,87,105]. As a result, instances with up to 100 demand nodes were addressed optimally in three hours or less [90].…”
Section: Solution Methodsmentioning
confidence: 99%
“…The most common economic factor was cost minimization. The often used cost elements were transportation [93,108], fixed and variable outsourcing [105], the use of vehicles [52,87,105], fuel consumption [109], penalty cost for arriving early or late [76], facility opening costs [77], and shortage costs for relief suppliers [79], etc.…”
Section: Economic Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the issues of investment attractiveness of this ICT tool remained unclear. The solution to this problem is contained in [11], which proposes a policy for the operation of multi-seat robots for room service traveling within the hotel. The study concluded that because multi-capacity jobs can serve many requests in a single trip, this operating policy can reduce the investment cost of operating the robots.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%